Modern paper crafts a 21st-century guide to folding, cutting, scoring, pleating, and recycling - Van Sicklen, Margaret (Stewart, Tabori & Chang, 2011)
More than 20 projects made using traditional paper craft techniques updated for the 21st century, from a leading author in the paper craft community.